Moral Education of Future Lawyers while Studying German Language - Arterchuk, Tetiana (Pedagogical Discourse, 2012)
The article deals with the possibilities of educational influence on future legal professionals by means of German languauge. The author emphasizes the moral potential which includes the content of foreign language training (literary extracts, proverbs, phrases) as well as the form of the lesson (communicative exercises, pair and group work, role-playing games)